Separating Active and Passive Influences on Stomatal Control of Transpiration. Issue 4 (31st January 2014) - McAdam, Scott A.M.; Brodribb, Timothy J.
Abstract : Stomatal closure during water stress in the conifer Metasequoia glyptostroboides transitions from being entirely passive under moderate water stress to predominantly active, mediated by the level of foliar ABA, under more severe water stress . Abstract: Motivated by studies suggesting that the stomata of ferns and lycophytes do not conform to the standard active abscisic acid (ABA) -mediated stomatal control model, we examined stomatal behavior in a conifer species ( Metasequoia glyptostroboides ) that is phylogenetically midway between the fern and angiosperm clades. Similar to ferns, daytime stomatal closure in response to moderate water stress seemed to be a passive hydraulic process in M. glyptostroboides immediately alleviated by rehydrating excised shoots. Only after prolonged exposure to more extreme water stress did active ABA-mediated stomatal closure become important, because foliar ABA production was triggered after leaf turgor loss. The influence of foliar ABA on stomatal conductance and stomatal aperture was highly predictable and additive with the passive hydraulic influence. M. glyptostroboides thus occupies a stomatal behavior type intermediate between the passively controlled ferns and the characteristic ABA-dependent stomatal closure described in angiosperm herbs. These results highlight the importance of considering phylogeny as a major determinant of stomatal behavior.